Epidemiology-based Analysis of Characteristics of Dual Infection of Tuberculosis /Acquired Immune Deficiency Syndrome (AIDS) and Drug Resistance Mechanism of Related Genes: Dual Infection of TB/AIDS and Drug Resistance Mechanism Genes - Yang, Jingjing; Zheng, Xiaoyan; Zhang, Shuai; Wang, Hanwei (Cellular and Molecular Biology, 2022)
This research was to explore the population characteristics and drug-resistant gene mutations of tuberculosis (TB) and human immunodeficiency virus (HIV)/acquired immune deficiency syndrome (AIDS) dual infection population, and to provide a reference for clinical screening and prevention of TB/HIV dual infection. TB patients and HIV-infected/AIDS patients registered in Fuzhou Center for Disease Control and Prevention were selected as research subjects. The population characteristics of TB/HIV dual infection and mutation of drug-resistant genes were discussed. It was found that TB patients aged 20-40 years had the highest HIV infection rate, followed by those aged over 40 years. The rate of HIV infection in smear-negative TB patients was higher than that in smear-positive TB patients. HIV/AIDS patients aged 20-40 had the highest TB infection rate. In addition, men had higher rates of HIV than women, and married people had lower rates of HIV than single people. Mycobacterium tuberculosis (MTB) had the highest resistance to isoniazid (42.86%), followed by ofloxacin (34.82%), streptomycin (33.81%), and rifampicin (32.15%). Among the 113 cases of multi-drug resistant strains, 82 cases had mutations in the rpoB gene, with a gene mutation rate of 55.75%. The mutations ranged from codon 511 to codon 569. A total of 31 cases had mutations in the katG/inhA gene. Of which, there were 17 cases of katG single gene mutation, 9 cases of inhA single gene mutation, and 5 cases of combined katG and inhA gene mutation. It was suggested that it was necessary to carry out key TB/HIV two-way screening for TB patients older than 40 years old/smear-negative and male, single, and HIV-infected/AIDS patients aged 20-40. The resistance of MTB to antiTB drugs in this area was generally high, and the drug resistance of retreated patients was significantly higher than that of newly treated patients. Among the resistance genes, the rpoB gene had the highest mutation frequency, followed by the katG gene and inhA gene.